Aerosol Typology and Trajectories in the Metropolitan Region of Rio de Janeiro, Brazil (Global Journal of Human-Social Science, 2023)
Aerosols are liquid or solid particles suspended in the atmosphere. Correct determination of the distribution of aerosol types in the atmosphere is of paramount importance for long-term climate predictions. The latest report of the International Panel on Climate Change (IPCC) addresses aerosols as representing the most significant uncertainties in the context of forcing climate sources. These particles can interfere with the climate directly, indirectly, or semi-directly. Directly, we can highlight the interaction of these particles with solar radiation through their scattering or absorption. Indirectly, the role of these aerosols as nuclei for the condensation of liquid and ice in clouds is significant. Depending on their quantity, these aerosols can form larger or smaller droplets, leading to changes in the cloud's albedo. As for semi-direct effects, we can emphasize the role of aerosols as radiation absorbers within clouds, consequently leading to changes in the stability of the air parcel. As a semi-direct effect, we can highlight changes in the life cycle and the ability to make convective clouds colder and more profound.
Keywords: aerosol; optical depth; CALIPSO; hysplit